2015
DOI: 10.1038/srep15985
|View full text |Cite
|
Sign up to set email alerts
|

Targeting extra-oral bitter taste receptors modulates gastrointestinal motility with effects on satiation

Abstract: Bitter taste receptors (TAS2Rs) are present in extra-oral tissues, including gut endocrine cells. This study explored the presence and mechanism of action of TAS2R agonists on gut smooth muscle in vitro and investigated functional effects of intra-gastric administration of TAS2R agonists on gastric motility and satiation. TAS2Rs and taste signalling elements were expressed in smooth muscle tissue along the mouse gut and in human gastric smooth muscle cells (hGSMC). Bitter tastants induced concentration and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
172
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(181 citation statements)
references
References 36 publications
8
172
0
1
Order By: Relevance
“…Comparing the two 322 studies is difficult due to species and sex differences and also differences in the dosage. The Furthermore, bitter compounds induced concentration and region-dependent contractility 329 changes in mouse intestinal muscle strips (13). 330 However, the current study does not rule out that the findings related to the administration 331 of DB are mediated via a different pathway.…”
mentioning
confidence: 38%
See 3 more Smart Citations
“…Comparing the two 322 studies is difficult due to species and sex differences and also differences in the dosage. The Furthermore, bitter compounds induced concentration and region-dependent contractility 329 changes in mouse intestinal muscle strips (13). 330 However, the current study does not rule out that the findings related to the administration 331 of DB are mediated via a different pathway.…”
mentioning
confidence: 38%
“…291 In addition we found that in women, but not in men, there was a switch in the origin of phase (22). A dose of 1 µmol/kg DB was chosen since this dosage 296 significantly inhibited gastric accommodation without inducing adverse events (13). Also in 297 the present study no adverse events were reported by the volunteers.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…This hypothesis has been verified by measuring the effect of HED on gastric motility in strips of stomach dissections in an organ bath. Avau et al (37) demonstrated that bitter compounds such as denatonium benzoate increased contractility in gastric strips of mice and caused an impairment of gastric relaxation after intragastric infusion. Whether a bittermasking compound has opposite effects by causing gastric relaxation is an open question.…”
Section: Discussionmentioning
confidence: 99%